1998
DOI: 10.1046/j.1360-0443.1998.931218399.x
|View full text |Cite
|
Sign up to set email alerts
|

Illicit drug use among Mexicans and Mexican Americans in California: the effects of gender and acculturation

Abstract: Acculturation and United States nativity are risk factors for illicit drug use among Mexican origin men and women. However, women have increased vulnerability compared with men. Findings reinforce the need for culturally based public health interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
154
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(177 citation statements)
references
References 8 publications
(9 reference statements)
16
154
6
Order By: Relevance
“…This finding is similar to other studies of methamphetamine use among heterosexuals (CDC, 2006;Molitor et al, 1998;Zule et al, 2007). Higher acculturation has previously been shown to be associated with illicit drug use among Mexican immigrants (Vega et al, 1998), similar to the association with methamphetamine/ cocaine use found in our study. Previous studies of Mexican migrants have also reported the common practice of having sex with sex workers, where a network of men may be linked by one or more female sex workers, which consequently generates the potential for multiple infections at one site (Organista & Organista, 1997;Painter, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…This finding is similar to other studies of methamphetamine use among heterosexuals (CDC, 2006;Molitor et al, 1998;Zule et al, 2007). Higher acculturation has previously been shown to be associated with illicit drug use among Mexican immigrants (Vega et al, 1998), similar to the association with methamphetamine/ cocaine use found in our study. Previous studies of Mexican migrants have also reported the common practice of having sex with sex workers, where a network of men may be linked by one or more female sex workers, which consequently generates the potential for multiple infections at one site (Organista & Organista, 1997;Painter, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…7,19,20,29 Additionally, interactions between gender and ethnicity or acculturation were also tested because of potential for gender to moderate the relationships between our cultural variables and health outcomes (for instance to detect if drug use was particularly prevalent in White boys or marginalised Latinas). 6,7,9 In no case was such an interaction term signi cant (p . 0.05), nor did any model with the interaction term signi cantly (p .…”
Section: Health Risk Behavioursmentioning
confidence: 99%
“…Some studies suggest more acculturated Latinos exhibit more risk behaviours, [6][7][8][9] while others suggest less acculturation is associated with higher risk. 10,11 Much of the inconsistency in the acculturation and health behaviour literature has been the result of attempts to combine Latinos from different regions as well as the use of more limited models of cultural change in such studies.…”
mentioning
confidence: 99%
“…Wells et al (1987) reported that Mexican Americans with a DIS/DSM-III diagnoses in the past six-months were twice as likely to receive care from a general medical practitioner than from a mental health specialist. Cultural interpretation of symptoms, stigma related to mental illness and its treatments, somatization of psychiatric symptoms, and the availability of general medical providers are believed to explain why less acculturated Latinos and immigrants underutilize specialty mental health services and rely more often on the general medical sector for care than more acculturated Latinos (Castillo, Waitzkin, & Escobar, 1994;Escobar, Burnam, Karno, Forsythe, & Golding, 1987;Vega et al, 1998). Future research is needed to clarify what aspects of the acculturation experience influence mental health service use decisions among Latinos and how it interacts with other predisposing, enabling and need factors.…”
Section: Correlates Of Service Use-mentioning
confidence: 99%